Analysis of Inflectional Morpheme in a McMahon’s Speech “Our Department’s Final Mission” - Nasywa Maulidina Zahra Gumilar; Otong Setiawan Djahari (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2026)
Inflectional morphemes are of great importance in linguistic analysis, especially when applied to speech delivered in various contexts. We explore the complexity of inflectional morphemes through an analysis of Linda McMahon’s Speech script titled “Our Department’s Final Mission.” Inflectional morphemes are also known as grammatical morphemes, as their primary function is to provide grammatical information about a word without altering its core meaning or lexical category. These inflectional morphemes include possessive morphemes (-‘s/s’), plural morphemes (-s/es), third-person singular present morphemes (-s), past morphemes(-d/ed), present/progressive particles (-ing), past participle (-en), comparative particles (-er), and superlative particles (-est). Therefore, this study focuses on understanding the types of inflectional morphemes used in Linda McMahon’s speech script. The main theory of inflectional morphemes is based on an understanding of grammatical function, affixation processes, and categories in the language system. The researcher identified 7 categories of inflectional morphemes. The result showed that 99 inflectional morphemes were found in Linda McMahon’s speech script. There were 46 plural morphemes (-s), 26 present/progressive particle morphemes (-ing), 19 past tense morphemes (-ed), 4 possessive morphemes (-‘s/s’), 2 third-person singular present morphemes (-s),1 comparative morpheme (-er), and 1 superlative morpheme (-est). It can be conclude that the most dominant category in the analysis is the plural morpheme (-s) and the least dominant is the comparative (-er) and superlative (-est) morpheme. Its is hoped that this study can provide solutions in determining the types of inflectional morphemes in a speech script.